Bridging the extracellular vesicle knowledge gap: insights from non-mammalian vertebrates, invertebrates, and early-diverging metazoans - Liegertová, Michaela; Janoušková, Olga (Frontiers in Cell and Developmental Biology, 2023)
Extracellular vesicles (EVs) are lipid-enclosed structures that facilitate intercellular communication by transferring cargo between cells. Although predominantly studied in mammals, EVs are ubiquitous across metazoans, and thus research in non-mammalian models is critical for fully elucidating EV biology. Recent advances demonstrate that EVs mediate diverse physiological processes in non-mammalian vertebrates, including fish, amphibians, and reptiles. Piscine EVs promote fin regeneration in zebrafish and carry heat shock proteins regulated by stress. Frog EVs containing microRNAs modulate angiogenesis, while turtle EVs coordinate reproductive functions. Venom from snakes contains EVs that mirror the whole venom composition and interact with mammalian cells. Invertebrates also possess EVs involved in immunity, development, and pathogenesis. Molluscan EVs participate in shell formation and host interactions. Arthropod models, including Drosophila, genetically dissect conserved pathways controlling EV biogenesis and signalling. Nematode EVs regulate larval development, animal communication, and ageing via conserved EV proteins. Ancient metazoan lineages utilise EVs as well, with cnidarian EVs regulating immunity and regeneration. Ultimately, expanding EV research beyond typical biomedical models to encompass phylogenetic diversity provides an unparalleled perspective on the conserved versus specialised aspects of metazoan EV roles over 500 million years. With a primary focus on the literature from the past five years, this review aims to reveal fundamental insights into EV-mediated intercellular communication mechanisms shaping animal physiology.